A study of the strategic alignment of information services with the 2030 Agenda: contributions of performance evaluation and sectoral standardization - Gaspar Pinto, Leonor; Ochôa, Paula (Advanced Notes in Information Science, 2023)
Compliance with the 2030 Agenda implies an increase in the capacity of organizations for strategic alignment, playing a connecting role and integrating different perspectives for valuing sectoral contributions. With the aim of contributing to the debate on the priority challenges posed by global references, CHAM – Centro de Humanidades promoted a study guided by the research question How can standardization contribute to the strategic alignment of the performance of information services with Sustainable Development Goals? Based on an interdisciplinary view of Information Science, Research in Evaluation and Evidence-Based Practice, this predominantly qualitative exploratory study is focused on the intersection of international standards on Performance Evaluation of Information Services with Sustainable Development, using two analyses: a) Macro: to examine the strategy and initiatives of ISO alignment with the 2030 Agenda, highlighting the standardization activities promoted by ISO/TC 46; and b) Micro: to explore the incorporation into international standards of performance indicators that allow evidence collection of the contribution of information services. Based on the examination of the 12 indicators defined for the nine goals of SDG 4 and the ISO 11620’s performance indicators, the area of competence development was identified as a strategic alignment point, leading to the development of two indicators - one focused on the development of ICT skills supported by libraries and the other, focused on functional literacy and numeracy of its us-ers, both relevant to highlight libraries’ contributions to the 2030 Agenda.